2020
DOI: 10.1371/journal.ppat.1008269
|View full text |Cite
|
Sign up to set email alerts
|

RNA decay during gammaherpesvirus infection reduces RNA polymerase II occupancy of host promoters but spares viral promoters

Abstract: In mammalian cells, widespread acceleration of cytoplasmic mRNA degradation is linked to impaired RNA polymerase II (Pol II) transcription. This mRNA decay-induced transcriptional repression occurs during infection with gammaherpesviruses including Kaposi's sarcomaassociated herpesvirus (KSHV) and murine gammaherpesvirus 68 (MHV68), which encode an mRNA endonuclease that initiates widespread RNA decay. Here, we show that MHV68induced mRNA decay leads to a genome-wide reduction of Pol II occupancy at mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…Lytic infection is frequently understood as a coordinated cascade of gene expression, characterized by genome-wide transcription (Pellett and Roizman, 2013). High resolution mapping of coding and non-coding viral RNAs (Cheng et al, 2012; O’Grady et al, 2019) and new molecular insights into the regulation of viral RNA transcription and abundance (Hartenian et al, 2020) have further refined models of lytic gene expression. Despite these advances, most studies have analyzed bulk cell populations, obscuring intercellular heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Lytic infection is frequently understood as a coordinated cascade of gene expression, characterized by genome-wide transcription (Pellett and Roizman, 2013). High resolution mapping of coding and non-coding viral RNAs (Cheng et al, 2012; O’Grady et al, 2019) and new molecular insights into the regulation of viral RNA transcription and abundance (Hartenian et al, 2020) have further refined models of lytic gene expression. Despite these advances, most studies have analyzed bulk cell populations, obscuring intercellular heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293Ts were made to stably express 633 doxycycline(dox)-inducible wild-type muSOX and its catalytically-dead D219A mutant by 634 PCR amplifying the aforementioned coding sequences from Addgene plasmids 131702 635 and 131704 using the muSOX F/R primers (see Key Resources Table) and InFusion 636 cloning these fragments into the Lenti-X TM Tet-One TM Inducible Expression System 637 digested with AgeI. Lentivirus was made for both constructs by transfecting 293T cells 638 with second generation packaging plasmids and spinfected onto 293T cells at a low 639 multiplicity of infection (MOI) as previously described (Hartenian et al, 2020). 24 hr 640 later, 350 µg/ml zeocin was added to select for transduced cells.…”
Section: Star Methods 620mentioning
confidence: 99%
“…In this study, we found that the 5'UTR of IFNAR1 mRNA renders it susceptible to cleavage by 2280 p30 because substitution of the 5'UTR of IFNAR2 mRNA by that of IFNAR1 mRNA conferred susceptibility to 2280 p30-induced mRNA degradation. Variable nucleotide sequences between the 5'UTR of A recent study demonstrated that MHV68-induced mRNA decay during lytic infection also leads to a genome-wide reduction of Pol II occupancy at mammalian promoters, which accelerates host mRNA decay [59]. Whether FCV-induced mRNA decay also contains a similar mechanism need to be further investigated.…”
Section: Plos Pathogensmentioning
confidence: 99%